Integrated control technology for radiation and scattering characteristics with separated surrounding units of plasmas - Changshi Yan; Peiqi Chen; Qiuyue Nie; Zhonglin Zhang; Ao Liu; Xin Ai; Guoqiang Wei; Xiaogang Wang (AIP Advances)
In the design of intelligent antennas, the integrated dynamic control of radiation and scattering characteristics is a core technology to improve antenna performance and broaden application scenarios. In this paper, such an electrically small antenna is designed by integrating an inner plasma layer for communication enhancement and an outer array composed of discrete cylindrical subwavelength plasma units for cloaking to radar detection. Numerical simulations are carried out with results indicating that the designed structure has synergistic modulation capability for improving radiation characteristics and controlling scattering properties simultaneously. It is shown that the inner subwavelength plasma ring provides a radiation gain of over 10 dB for the communication in the L-band, while the outer design of discrete surrounding units dominates omnidirectional suppression of radar cross section by ∼−15 dBsm. Meanwhile, both globally and locally fine-tuning parameters of the outer plasma units can achieve a transformation in forward- and backward-dominated scattering modes. Furthermore, the design of outer plasma units with heterogeneous plasma parameters enables possibilities of implementing targeted and more flexible scattering patterns. Our results offer practical solutions for designing various plasma-based tunable, reconfigurable, and multifunctional electromagnetic devices.